Manufacturing and morphology of poly(epsilon-caprolactone) based microfibre webs for biomedical applications through airbrush technique - Bedeloğlu, Ayşe; Bhullar, Sukhwinder Kaur; Borazan, Ismail; Cin, Zeynep Islek; Demir, Ali (Natl Inst Science Communication-Niscair, 2017)
The objective of this study is to fabricate poly(epsilon-caprolactone) (PCL)-based micro/nano fibrous structures by using different types of solvents and nozzle sizes and to investigate the morphology of fabricated airbrushed structures for future biomedical applications. It is observed from the morphology and diameter of micro/nanofibres structures based on nozzle size, concentration of PCL and solvents, that these airbrushed biocompatible and biodegradable webs offer a potential in the medical field requiring direct, rapid and conformable applications.
Keywords: Airbrush technique; Biodegradable fibre; Microfibre; Nanofibre; Poly(epsilon-caprolactone)